Onomatopoeia Types and Translation Strategies: A Case Study on the Webtoon "Lore Olympus" - Kho, Vanesa; Gozali, Kezia Karina; Susilo, Jordan Yehezkiel; Santoso, Wulandari (SALEE: Study of Applied Linguistics and English Education, 2024)
Translating webtoon poses a challenge for the translator. However, many research focus on the application of comic translation instead of webtoon translation. Due to this, the research focused on finding out the translation technique used to translate the onomatopoeia in Lore Olympus from English to Indonesian. This case study was employed to analyze and interpret the translation techniques used, with case study to analyze the onomatopoeia. Content analysis and purposive sampling method was used to interpret the data between chapter 1 to chapter 50. The result of this study showed a total of 356 onomatopoeias in English and 355 in Indonesian; direct onomatopoeia was dominantly used, followed by exemplary onomatopoeia, and associative onomatopoeia as the least used. Out of seven translation technique, four was used: equivalence was used 69.5% times, borrowing was used 17.37% times, literal translation was used 11.8% times, and modulation was used 1.3% times. These translation techniques were applied to achieve meaning transfer and naturalness for the readers. However, some issues were found, for readers reading the translated webtoon, which might affect their reading experience negatively: typo, loss in artist’s intended phonetic meaning, improper expression of message, etc. The research proposed some recommendations for future researchers and translators.